Le labyrinthe littéraire de Mohamed Mbougar Sarr - Burnautzki, Sarah; Imorou, Abdoulaye; Ruhe, Cornelia (Francopolyphonies, 2025)
"Since his debut with the short story "La Cale" in 2014, Mohamed Mbougar Sarr's texts have enjoyed increasing success. Terre ceinte in 2015, Silence du chœur in 2017 and De purs Hommes in 2018 have all won major literary prizes. Finally, in 2021, with La plus secrète Mémoire des hommes, the jury for the Prix Goncourt opted for a novel that offers a subtle, detailed and lucid literary metareflection on the history of African literature and the Parisian literary milieu. This volume seeks to shed light on the narrative modalities that allow the author to transform politics into literature, but also to situate his work in the current literary context"--